다발성 공장 게실 천공으로 인한 급성 복막염 - 이봉규(Bong Gyu Lee); 박성배(Sung Bae Park); 변창규(Chang Gyoo Byun); 고영택(Young Taeg Koh); 서동엽(Dong Youb Suh); 박동선(Dong Sun Park); 강문자(Moon Ja Kang); 이권전(Kwun Jun Lee) (Annals of surgical treatment and research, 2004)
We report the case of a 77-year-old woman who presented with periumbilical pain from perforation of jejunal diverticula. The patient underwent surgery and multiple jejunal diverticula were found distributed from 30 cm to 60 cm distal to the ligament of Treitz. A segment of the jejunum containing all diverticula was resected and end-to-end anastomosis was performed. The postoperative course was uneventful. The patient continued to do well at last follow-up, 26 months after operation. Diverticulum of the jejunum is uncommon and the majority of patients are asymptomatic. Symptoms indicating diverticulum are few and often nonspecific; they may present either as generalized abdominal pain associated with intestinal disturbances or in more serious case, they can lead to complications requiring emergency surgery. In light of these considerations, we thought it useful to report a case of complicated multiple jejunal diverticula and draw attention to its complications that can be a source of gastrointestinal symptoms. KCI Citation Count: 1